Tourists Perceptions and Satisfaction Regarding Tour Guiding in the Republic of North Macedonia - Naumov, Kliment (European Journal of Multidisciplinary Studies, 2020)
Tourism is diverse industry and therefore it involves many different stakeholders for it operational activities. An essential element for sustainable tourism development in any tourist destination is the participation of active stakeholders and the cooperation between them. Among all, the tour guides play a major role in the tourism industry since tourists need to have a clear picture of the country and its offer, laws, rules and regulations and other expected behavioral patterns. Moreover, guides should have the ability to transform the tourist visit into an unforgettable experience. In addition to the quality and ability of tourist guides, there are many problems and issues associated with their services that can impact the ultimate satisfaction of tourists. In the Republic of North Macedonia, there is a positive trend in tourist guiding in the last 20 years. It is because of this fact that this paper pays attention to the role and importance of tour guiding for the Macedonian tourism.
Keywords: tourism, tourist destination, tourist experience, tour guides, tour guiding, empirical research